Asymmetric response of soil methane uptake rate to land degradation and restoration: Data synthesis. (6th September 2020) - Wu, Junjun; Chen, Qiong; Jia, Wei; Long, Chunyan; Liu, Wenzhi; Liu, Guihua; Cheng, Xiaoli
Abstract: Land degradation and restoration profoundly affect soil CH4 uptake capacity in terrestrial ecosystems. However, a comprehensive assessment of the response of soil CH4 uptake to land degradation and restoration at global scale is not available. Here, we present a global meta‐analysis with a database of 228 observations from 83 studies to investigate the effects of land degradation and restoration on the capacity of soil CH4 uptake. We found that land degradation significantly decreased the capacity of soil CH4 uptake, except the conversion of pasture to cropland where the soil CH4 uptake rate showed no response. In contrast, all types of land restoration significantly increased the capacity of soil CH4 uptake. Interestingly, the response of soil CH4 uptake rate to land degradation and restoration was asymmetric: the increased soil CH4 uptake rate in response to the land restoration was smaller compared to the decrease in CH4 uptake rate induced by the land degradation. The effect of land degradation on soil CH4 uptake rate was not dependent on the time since land use change, but the CH4 sink strength increased with the time since land restoration. The response of soil CH4 uptake rate to both land degradation and restoration was predominantly regulated by changes in the soil water‐filled pore space, soil bulk density, and pH, whereas alterations in the substrate quantity and quality had negligible effect. Additionally, the effects of land degradation and restoration on soil CH4 uptake were strongly related to the mean annual precipitation and soil texture. Overall, our results provide novel insights for understanding of how land degradation and restoration can affect the CH4 sink strength of upland soils, and more importantly, our findings are beneficial to take measures to enhance the potential of soil CH4 uptake in response to global land use change. Abstract : The capacity of soil CH4 uptake decreased rapidly in response to land degradation, and it was not dependent on the time since land use change. In contrast, land restoration significantly increased the capacity of soil CH4 uptake. But the recovery of the capacity of soil CH4 uptake was slow and it would take several decades.